Escolha e permanência de alunos no curso de química oriundos de um cursinho popular - Moga, Beatriz Vianna [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The pre-university preparatory courses (PUPC) were created due to the lack of places offered by the entrance exams, besides guaranteeing the entrance of the elite children to higher education (HE). The popular class could not afford to pay a pre-university entrance exams for their children, so the popular pre-university preparatory courses (PPUPC) emerged. The São Paulo State University (UNESP) offers several PVP and, among them, the “Cursinho Unificado do Campus de Araraquara” (CUCA) which, in one of its centers, offers classes inside the Institute of Chemistry (IQ) of UNESP. There are few studies on PPUPC in the area of science education and the existing studies do not focus on socioeconomic disparities as a central theme of these spaces. Since the 1960s, sociologist Pierre Bourdieu investigates the school inequalities associated with class belonging, mainly through the concepts of cultural and economic capital, and seems to us to be a fundamental author to capture the specificity of PVP. Given these assumptions and gaps, this work investigated the factors that influenced the entrance and permanence in the chemistry course through the personal, school and academic trajectory of students of this undergraduate and postgraduate course from a PPUPC, CUCA. In order to reconstruct these trajectories, we built a large questionnaire with thirty-nine questions, which gathers data on class belonging, school and academic trajectories, and the students' cultural and economic capital volumes. The questionnaire was answered by 13 students, their results were submitted to quantitative analysis based on descriptive statistics and were analyzed according to Bourdieu's theories, mainly regarding economic and cultural capitals. We identified low volume of economic and cultural capital and concluded that, even so, there were factors that influenced the entry of these subjects to a public university, of quality, such as parents' involvement in their children's school life, activities developed during the high school and the course, support from teachers, attending trade fairs, the subject always thought about going to university, personal experience or motivation, tv information, radio, newspapers, official sources, internet, friends, other family members ... in addition, we identified factors that allowed the permanence of these subjects in the es as university aid, monitoring scholarship, scientific initiation, BAAE I or II, financial aid from parents or family, the fact that they reside in Araraquara.

Os cursinhos pré-vestibulares (CPV) surgiram em função da carência de vagas oferecidas pelos vestibulares, além de garantir o ingresso dos filhos da elite ao Ensino Superior (ES). A classe popular não tinha condições de pagar um CPV para os filhos, então surgiram os cursinhos pré-vestibulares populares (PVP). A Universidade Estadual Paulista (UNESP) oferece vários PVP e, dentre eles, merece destaque o Cursinho Unificado do Campus de Araraquara (CUCA) que, em um dos seus polos, oferece aulas no interior do Instituto de Química (IQ) da UNESP. Há poucos estudos sobre os PVP na área de Educação em Ciências e os estudos que existem não focam nas disparidades socioeconômicas como tema central desses espaços. O sociólogo Pierre Bourdieu desde a década de 60 investiga as desigualdades escolares associadas ao pertencimento de classe, principalmente por meio dos conceitos de capital cultural e econômico, e nos parece um autor fundamental para captar a especificidade dos PVP. Diante dessas premissas e lacunas, esse trabalho investigou os fatores que influenciaram a entrada e permanência no curso de química através da trajetória pessoal, escolar e acadêmica de estudantes desse curso de graduação e pós-graduação oriundos de um PVP, o CUCA. Para reconstruir essas trajetórias construímos um questionário amplo, com trinta e nove questões (três abertas e trinta e seis fechadas), que levanta dados sobre o pertencimento de classe, as trajetórias escolares e acadêmicas e os volumes de capitais culturais e econômicos dos estudantes. O questionário foi respondido por 13 estudantes, cujos resultados foram submetidos à análise quantitativa com base na estatística descritiva e foram analisados de acordo com a teoria de Bourdieu, principalmente quanto aos capitais econômico e cultural. Identificamos baixo volume de capital econômico e cultural e concluímos que, mesmo assim tiveram fatores que influenciaram na entrada desses sujeitos a universidade pública, de qualidade, como envolvimento dos pais na vida escolar dos filhos, atividades desenvolvidas durante o Ensino Médio e o cursinho, apoio dos professores, comparecimento à feiras de profissões, o sujeito sempre pensou em ir para a universidade, experiência ou motivação pessoal, informações da TV, rádio, jornais, fontes oficiais, internet, amigos, outros familiares. Além disso, identificamos fatores que permitiram a permanência desses sujeitos no ES como auxílio da universidade, bolsa de monitoria, iniciação científica, Bolsa de Apoio Acadêmico e Extensão (BAAE) I ou II, auxílio financeiro por parte de pais ou familiares, o fato deles residirem em Araraquara.
Popular pre-university preparatory course student's choice and persistence in a chemistry course
Keywords: Cursinhos populares; Trajetórias; Alunos de química; Bourdieu